CERTAINTY OF EMPLOYMENT RELATIONSHIP FOR PKWT WORKERS WHO RESIGN BEFORE THE END OF THE EMPLOYMENT AGREEMENT - Risna Menda Lovinta Siregar (International Journal of Educational Review, Law And Social Sciences (IJERLAS), 2025)
An employment agreement is defined by Law Number 13 of 2003 concerning employment as an agreement between workers or laborers and employers or employers that contains the terms of employment, rights and obligations of the parties. It is a logical consequence that in an employment agreement, the position of the employer as an employer is always higher than the position of the worker or laborer. There are two reasons behind this, namely economic reasons and psychological reasons. This study aims to determine the certainty of status for PKWT workers who resign before the end of the employment agreement. The research method used in this study is a normative research method that refers to legal principles and laws and regulations. The results of this study indicate that the party that terminates the employment relationship is required to pay compensation in the amount of the worker's/laborer's wages until the end of the employment agreement. This provision regulates the employment agreement for workers who resign before the end of the employment agreement so that workers can be certain regarding their rights and obligations.